Trends in Website Development Based on the Chosen Functionalities in Qualitative Aspect - Garczarek-Bąk, Urszula (Studia Oeconomica Posnaniensia, 2016)
The aim of this paper is to examine the essential features of every good business website. This article presents the ways of improving both the efficiency of website and the performance of the system. The methodology is based on literature research and Internet resources, since those are the most up to date information sources about new trends in web page development. The key elements of a high quality website (including site characteristics) and crucial information that indicates the quality of the content were analyzed. Particular attention was devoted to the trends driving the future of websites that could result in significant image improvement without high expense. Most websites have flaws for a number of reasons, not only related to the limitation of resources, but also due to the ignorance or inattention of webmasters, so the website quality aspects in relation to new trends, identified in this paper, can be used as insights for the improvement of web pages' quality.